2016
DOI: 10.1155/2016/3684965
|View full text |Cite
|
Sign up to set email alerts
|

Exome Sequencing Identifies Compound Heterozygous Mutations inSCN5AAssociated with Congenital Complete Heart Block in the Thai Population

Abstract: Background. Congenital heart block is characterized by blockage of electrical impulses from the atrioventricular node (AV node) to the ventricles. This blockage can be caused by ion channel impairment that is the result of genetic variation. This study aimed to investigate the possible causative variants in a Thai family with complete heart block by using whole exome sequencing. Methods. Genomic DNA was collected from a family consisting of five family members in three generations in which one of three childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
8
0
1
Order By: Relevance
“…Additionally, since one autism-affected child, 2.III-2, of family number 2 had heart block along with ASD, a cause of this heart defect was explored in our previous publication. The previous result revealed that autism and heart block in this family are coincidental, not likely to be Timothy syndrome [ 18 ].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Additionally, since one autism-affected child, 2.III-2, of family number 2 had heart block along with ASD, a cause of this heart defect was explored in our previous publication. The previous result revealed that autism and heart block in this family are coincidental, not likely to be Timothy syndrome [ 18 ].…”
Section: Discussionmentioning
confidence: 82%
“…The family number 2 had three generations, of whom four out of seven members were available for DNA study, an unaffected grandmother (2.I-2), an unaffected mother (2.II-2), and two children with autism (2.III-2 and 2.III-3). The proband of the family number 2 (2.III-2) had also been included in another study [ 18 ]. The clinical information of both families is shown in Supplementary 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Increasing evidence suggests that gene mutations and dysfunction of the conduction system during heart development may result in familial AVB [9][10][11][12] . However, only a few data are available regarding the pathophysiology of acquired AVB.…”
Section: Discussionmentioning
confidence: 99%
“…Progressive idiopathic fibrosis related to an aging process of the cardiac skeleton is the most common cause of chronic acquired AVB 2,[4][5][6][7][8] . It is generally accepted that familial and inherited AVB are caused by gene mutations and dysfunction of the conduction system during heart development [9][10][11][12] . In contrast, the pathophysiological mechanism of acquired AVB is currently unclear.…”
mentioning
confidence: 99%
“…Ген SCN5A (sodium voltage-gated channel alpha subunit 5, 3p22.2) кодирует α-субъединицу натриевого канала. Дефекты гена связаны с развитием синдрома удлиненного интервала QT (LQT3) [17].…”
Section: Sri Of Therapy and Prevention Medicine -Branch Of Fsbsi Fedeunclassified